2015
DOI: 10.1177/1535370215587918
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rb1 inhibits matrix metalloproteinase 13 through down-regulating Notch signaling pathway in osteoarthritis

Abstract: Mounting evidence suggests that an excess of matrix metalloproteinase-13 (MMP-13) plays an important role in the breakdown of extracellular matrix in osteoarthritis (OA). Here, the effects of ginsenoside Rb1 (GRb1) on the expression of MMP-13 in IL-1β-induced SW 1353 chondrosarcoma cells and an experimental rat model of OA induced by anterior cruciate ligament transection (ACLT) were investigated. SW1353 chondrosarcoma cells were pretreated with or without GRb1 and Notch signaling pathway inhibitor, DAPT, then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Whereas it downregulates the ECM catabolic factors MMP-1 and MMP-13 [ 40 , 41 ]. Additionally, MMP-13 is positively associated with Notch signaling, which can be suppressed by Rb1 [ 82 ]. Pinocembrin, a flavonoid extracted from propolis, inhibits the nuclear translocation of p65 and phosphorylation and degradation of I κ B α induced by TNF α in human chondrocytes, leading to suppression of MMP-3 and MMP-13 expression [ 83 ].…”
Section: Anticatabolic Activity Of Tcmmentioning
confidence: 99%
“…Whereas it downregulates the ECM catabolic factors MMP-1 and MMP-13 [ 40 , 41 ]. Additionally, MMP-13 is positively associated with Notch signaling, which can be suppressed by Rb1 [ 82 ]. Pinocembrin, a flavonoid extracted from propolis, inhibits the nuclear translocation of p65 and phosphorylation and degradation of I κ B α induced by TNF α in human chondrocytes, leading to suppression of MMP-3 and MMP-13 expression [ 83 ].…”
Section: Anticatabolic Activity Of Tcmmentioning
confidence: 99%
“…Catabolic reactions take place in the OA cartilage, in which collagen and aggrecan are degraded [63]. MMPs are a family of zinc containing, calcium-dependent neutral proteases which can initiate the cleavage of type II collagen and aggrecan [76]. In OA chondrocytes, resveratrol may reverse the decrease in the levels of type II collagen, aggrecan, and glycosaminoglycan by regulating silent information regulator 2 type 1, hypoxia-inducible factor-2α, and MMPs expression [24,62,63,77].…”
Section: The Effects Of Bioactive Components On Cartilage In Oamentioning
confidence: 99%
“…In OA chondrocytes, resveratrol may reverse the decrease in the levels of type II collagen, aggrecan, and glycosaminoglycan by regulating silent information regulator 2 type 1, hypoxia-inducible factor-2α, and MMPs expression [24,62,63,77]. Curcumin [28], naringin [42], icariin [16,78,79], berberine [68,69], sinomenine [72], tetramethylpyrazine [13,70,80], astragaloside IV [81], halofuginone [82], puerarin [83], quercetin [84], celastrol [54,85], harpagoside [32], ferulic acid [55], shikonin, acetylshikonin [86], ginsenoside Rb1 [76,87], cinnamophilin [30], honokiol [50], 2, 3, 5, 4′-tetrahydroxystilbene-2-O-β-d-glucoside [60], geniposide [31], ginsenoside Rg5 [74], cryptotanshinone [29], isofraxidin [33], paeonol [56], crocin [43], coptisine [44], piperine [45], butein [46], licochalcone A [36], tectorigenin [48], theaflavin-3,3′-digallate [59], anemonin [49], gastrodin [51], compound K…”
Section: The Effects Of Bioactive Components On Cartilage In Oamentioning
confidence: 99%
See 1 more Smart Citation
“…Evidences have also shown that NOTCH1 is frequently activated in the chondrocytes of OA cartilage [ 22 , 23 , 24 , 25 ]. Inhibition of NOTCH1 activation by γ-secretase inhibitor restores the decreased expression of collagen II and suppresses MMP13 expression [ 26 ]. Hence, activation of NOTCH1 signaling likely plays an important role in the pathogenesis of OA.…”
Section: Introductionmentioning
confidence: 99%